The Use of AI In Digital Transformation Ethics and Public Relations Strategies - Tabitha Gloria Perangin Angin; Lusy Mukhlisiana (Publikasi Indonesia, 2024)
The use of artificial intelligence (AI) has become a significant trend in various sectors, including in public relations practice. This research aims to examine the ethics and strategies of using artificial intelligence in public relations practice. The research method used in this research is qualitative, which is based on literature review studies; data was collected from the Sinta Journal, Scopus, and Garuda Ristek Dikti databases. The scope and focus of the article search apply explicitly to the topic of ethics and Artificial Intelligence-based strategies using search queries based on the Google Scholar search engine. Supporting data comes from books and other relevant reference sources. The research results highlight the importance of maintaining balance and diversity of data and maintaining its confidentiality by applicable privacy regulations. Strategically, AI can help parse text to accurately identify public sentiment, improve interactions withchatbots and virtual assistants, and use recommendation systems based on browsing history or user interactions. The practical implications of this research emphasize the need for PR practitioners to develop transparent and responsible policies for managing data processed by AI, as well as ensuring its use is in line with organizational communication goals and to improve relations with the public. There are also opportunities for further research into the ethical and strategic implications of the use of AI in PR, as well as the development of more sophisticated methods for applying this technology in organizational communications contexts.